2002
DOI: 10.1074/jbc.m201999200
|View full text |Cite
|
Sign up to set email alerts
|

L-selectin Dimerization Enhances Tether Formation to Properly Spaced Ligand

Abstract: Selectin counterreceptors are glycoprotein scaffolds bearing multiple carbohydrate ligands with exceptional ability to tether flowing cells under disruptive shear forces. Bond clusters may facilitate formation and stabilization of selectin tethers. L-selectin ligation has been shown to enhance L-selectin rolling on endothelial surfaces. We now report that monoclonal antibodies-induced L-selectin dimerization enhances L-selectin leukocyte tethering to purified physiological L-selectin ligands and glycopeptides.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 48 publications
2
28
1
Order By: Relevance
“…Within these limits, cell velocity varied inversely with substrate density and consistently exhibited a minimum near a shear stress of 0.8 dynes/cm 2 , in good agreement with experimental measurements of the shear threshold for neutrophils adhering to PSGL-1. In a similar manner, we confirmed that dimerization of adhesion receptors promoted more robust rolling while leaving the magnitude of the shear threshold unaltered (34). Much like a doubling in substrate density, dimerizing L-selectin in our simulations resulted in slower cell rolling but an identical shear threshold at 0.8 dynes/cm 2 (Fig.…”
Section: Predicting Selectin-mediated Adhesion Dynamicssupporting
confidence: 71%
“…Within these limits, cell velocity varied inversely with substrate density and consistently exhibited a minimum near a shear stress of 0.8 dynes/cm 2 , in good agreement with experimental measurements of the shear threshold for neutrophils adhering to PSGL-1. In a similar manner, we confirmed that dimerization of adhesion receptors promoted more robust rolling while leaving the magnitude of the shear threshold unaltered (34). Much like a doubling in substrate density, dimerizing L-selectin in our simulations resulted in slower cell rolling but an identical shear threshold at 0.8 dynes/cm 2 (Fig.…”
Section: Predicting Selectin-mediated Adhesion Dynamicssupporting
confidence: 71%
“…Notably, although L-selectin ligation was reported to drive the selectin into raft microdomains and induce shedding (15), the chemokine-mediated suppressive signals studied in our system are not associated with L-selectin shedding, because chemokine-mediated suppression of L-selectin rolling cannot be rescued by inhibition of L-selectin shedding (20). Ab-driven dimerization of the ectodomain of L-selectin known to augment L-selectin adhesiveness under shear flow (46) was also unable to rescue chemokine-mediated destabilization of rolling (20). Our data are therefore consistent with the possibility that chemokinedriven GPCR assemblies do not interfere with the ability of Lselectin to dimerize, but rather inhibit key cytoplasmic associations of L-selectin necessary for adhesion stabilization under external forces (47).…”
Section: Discussionmentioning
confidence: 99%
“…Considering that all physiological ligands of L-selectin present multiple low-affinity oligosaccharide binding sites, inducible L-selectin clustering would likely provide a highly efficient means of regulating its binding activity. Indeed, L-selectin when clustered greatly enhances leukocyte tethering (12,48). This process also results in signaling and the induction of various postadhesion events, including oxidative burst, degranulation, cytokine expression, actin polymerization, and CD18 integrin activation (9,21,22,30,43,64,67,71,76,80,81).…”
mentioning
confidence: 99%